1995
DOI: 10.1172/jci117954
|View full text |Cite
|
Sign up to set email alerts
|

c-KIT expression enhances the leukemogenic potential of 32D cells.

Abstract: The growth of human leukemic cells in culture and in vivo is dependent upon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The leukemogenic potential of SCF driven c-KIT activation could be demonstrated by transfection of c-KIT into 32D cells with subsequent injection into syngeneic hosts. In contrast to animals injected with control 32D cells, these animals died of overwhelming leukemia [109]. Besides activation through SCF, c-KIT can also be mutationally activated.…”
Section: Genetic Abnormalities In Upstream Receptorsmentioning
confidence: 91%
“…The leukemogenic potential of SCF driven c-KIT activation could be demonstrated by transfection of c-KIT into 32D cells with subsequent injection into syngeneic hosts. In contrast to animals injected with control 32D cells, these animals died of overwhelming leukemia [109]. Besides activation through SCF, c-KIT can also be mutationally activated.…”
Section: Genetic Abnormalities In Upstream Receptorsmentioning
confidence: 91%
“…The constitutive activation of this essential signaling pathway might contribute to BZ's ability to induce acute myeloid leukemia. In support of this speculation, it has been reported that constitutive overexpression of the c-kit receptor in 32D myeloblasts results in a population of cells that when injected into the bone marrow of syngeneic mice results in acute leukemia in four to six weeks [51]. Experiments to test the leukemogenic capacity of HQ-treated, incompletely differentiated 32D myeloblasts in syngeneic mice are in progress.…”
Section: Il-3 Alonementioning
confidence: 92%
“…These were collected, concentrated, and checked for purity by silver stain. SLF was also conjugated with biotin (Sigma) as described (30).…”
Section: Methodsmentioning
confidence: 99%